HELLP syndrome and associated factors among pregnant women with preeclampsia/eclampsia at a referral hospital in southwestern Uganda: a cross-sectional study - Fadumo Mohamed Abdullahi; Yarine Fajardo Tornes; Richard Migisha; Paul Kato Kalyebara; Leevan Tibaijuka; Joseph Ngonzi; Musa Kayondo; Onesmus Byamukama; Stuart Turanzomwe; Joseph Rwebazibwa; Brenda Ainomugisha; Rogers Kajabwangu; et al. (BMC, 2024)
Abstract Background Hemolysis Elevated Liver Enzymes Low Platelets (HELLP) syndrome, a complication of preeclampsia/eclampsia, is associated with severe maternal morbidity and mortality. In resource-limited settings, such as Uganda, gaps in routine laboratory assessments may lead to underdetection of HELLP syndrome. This study determined the prevalence and factors associated with HELLP syndrome among pregnant women with preeclampsia/eclampsia at Mbarara Regional Referral Hospital (MRRH), southwestern Uganda. Methods A cross-sectional study was conducted at the high-risk ward of the MRRH from December 2022 to June 2023. Pregnant women diagnosed with preeclampsia or eclampsia were enrolled consecutively. Participants' sociodemographic and clinical data were collected using an interviewer-administered questionnaire. The diagnosis of complete HELLP syndrome was made based on the Tennessee classification: aspartate aminotransferase enzyme ≥ 70 IU/L, platelet counts < 100,000 cells/µL, and serum lactate dehydrogenase enzyme ≥ 600 IU/L. We used multivariable modified Poisson regression analysis to determine factors associated with HELLP syndrome. Results A total of 129 participants with a mean age of 28 ± 6.6 years were enrolled in the study. The prevalence of HELLP syndrome was 18.6% (n = 24; 95% CI: 12.7-26.3%). Independent factors associated with HELLP syndrome were maternal age (adjusted prevalence ratio [aPR]: 4.96; 95% CI: 1.57-15.65; for mothers aged < 20 years compared to those aged 20-34 years), the presence of epigastric pain (aPR: 5.89; 95% CI: 1.41-14.63), and referral from other health facilities (aPR: 3.14; 95% CI: 1.27-7.72). Conclusion Approximately 2 of the 10 women who presented with preeclampsia or eclampsia had HELLP syndrome. It is more common among teenage mothers, those with a history of epigastric pain and those referred from lower health facilities. Incorporating routine laboratory testing for HELLP syndrome in the diagnostic protocol for preeclampsia or eclampsia, especially among adolescent mothers, those experiencing epigastric pain, and those referred from lower health facilities, could enhance timely detection and management of mothers with preeclampsia whose pregnancies are complicated by HELLP syndrome.